Making Classic Wreaths : Designing & Creating for all Seasons - Smith, Ed, A.I.F.D. (New York Sterling Pub. Co., 2004)
Crafted from pinecones, seashells, autumn leaves, berries, pumpkins, and even styrofoam, they add a beautiful touch to any room all year long. They're easy to make, too, especially with instructions that carefully outline the basic supplies and show how to make an attractive bow, wire items to the wreath, work with dried materials, enhance pre-made wreaths, and much more.
Include index and Illustrations
Keywords: Wreaths